Effect of liquid and solid test meals on symptoms and gastric myoelectrical activity in patients with gastroparesis and functional dyspepsia. Issue 2 (11th April 2022) - Koch, Kenneth L.; Van Natta, Mark; Parkman, Henry P.; Grover, Madhusudan; Abell, Thomas L.; McCallum, Richard W.; Shaltout, Hossam A.; Sarosiek, Irene; Farrugia, Gianrico; Shulman, Robert J.; Tonascia, James; Miriel, Laura; et al.
Abstract: Background: Patients with gastroparesis (GP) and functional dyspepsia (FD) have similar symptoms, but the pathophysiology of postprandial symptoms remains uncertain. Aims: To compare symptoms and gastric myoelectrical activity (GMA) after liquid and solid test meals in patients with GP and FD. Methods: Patients enrolled in the Gastroparesis Clinical Research Consortium Registry were studied. Clinical characteristics were measured with standard questionnaires. GP was determined by 4‐h solid‐phase gastric scintigraphy. GMA was measured using electrogastrography before and after ingestion of a water load or nutrient bar on separate days. Symptoms were measured on visual analog scales. GMA responses to the water load for individual patients were also determined. Results: 284 patients with GP and 113 with FD were identified who ingested both test meals. Patients with GP and FD had similar maximal tolerated volumes of water [mean (SD) 378 (218) ml vs. 402 (226) ml, p  = 0.23] and reported similar intensity of fullness, nausea, bloating, and abdominal discomfort after the test meals. Twenty‐six percent and 19% of the patients with GP and FD, respectively, ingested subthreshold (<238 ml) volumes of water ( p  = 0.15). Gastric dysrhythmias were recorded in 66% of the GP and 65% of the FD patients after the water load. Symptoms and GMA were similar in both groups after ingestion of the nutrient bar. Conclusion: The similarity in GMA responses and symptoms after ingestion of solid or liquid test meals suggests GP and FD are closely related gastric neuromuscular disorders. Abstract : Patients with gastroparesis (GP) and functional dyspepsia (FD) have similar symptoms, but the pathophysiology of symptoms remains uncertain. Results show symptoms and gastric myoelectrical responses after ingestion of solid or liquid test meals are similar and suggests GP and FD are closely related gastric neuromuscular disorders.